2023
DOI: 10.1021/acssensors.2c02476
|View full text |Cite
|
Sign up to set email alerts
|

DNA Tetrahedron-Based Valency Controlled Signal Probes for Tunable Protein Detection

Abstract: Combined detection of multiple markers related to the same disease could improve the accuracy of disease diagnosis. However, the abundance levels of multiple markers of the same disease varied widely in real samples, making it difficult for the traditional detection method to meet the requirements of a wide detection range. Herein, three kinds of cardiac biomarkers, cardiac troponin I (cTnI), myoglobin (Myo), and C-reaction protein (CRP), which were from the pM level to the μM level in real samples, were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Multi-biomarkers can be sensed simultaneously by this approach, too. Through ligating different numbers of PtNPs at the endpoints of DNA tetrahedra, signal probes of varying valence states were obtained and used to detect cardiac markers with an adjustable detection range [ 151 ]. The aptamer-DNA tetrahedron complex has a synergistic structural advantage that can control the density of such probes and contribute to a renewable probe layer, avoiding nonspecific adsorption of targets on the surface and steric hindrance to the binding of target molecules [ 152 , 153 , 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multi-biomarkers can be sensed simultaneously by this approach, too. Through ligating different numbers of PtNPs at the endpoints of DNA tetrahedra, signal probes of varying valence states were obtained and used to detect cardiac markers with an adjustable detection range [ 151 ]. The aptamer-DNA tetrahedron complex has a synergistic structural advantage that can control the density of such probes and contribute to a renewable probe layer, avoiding nonspecific adsorption of targets on the surface and steric hindrance to the binding of target molecules [ 152 , 153 , 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…171 Yang et al successfully detected three types of cardiac biomarkers (cTnI, Mb, and CRP) at pM level to μM level using valency-controlled signal probes (trivalent, bivalent, and monovalent) based on DNA tetrahedron nanostructures (DTNs) and platinum nanoparticles (PtNPs). 172 This colorimetric assay indicates the risk level of heart disease which is based on the color depth as shown in Figure 6a(i): dark blue indicates low risk, and light blue indicates high risk. In addition, Figure 6a(ii) shows a 96-well plate for the specific detection process of the cTnI biomarker and the competitive reaction process on the surface of magnetic beads.…”
Section: Optical Signaling Readout-based Nanobiosensorsmentioning
confidence: 99%
“…The design and development of nanomaterial-based colorimetric sensors have utilized ideal inorganic chromophore metal nanoparticles such as AgNPs and AuNPs due to their tunable surface plasmon resonance properties and higher coefficients . Yang et al successfully detected three types of cardiac biomarkers (cTnI, Mb, and CRP) at pM level to μM level using valency-controlled signal probes (trivalent, bivalent, and monovalent) based on DNA tetrahedron nanostructures (DTNs) and platinum nanoparticles (PtNPs) . This colorimetric assay indicates the risk level of heart disease which is based on the color depth as shown in Figure a­(i): dark blue indicates low risk, and light blue indicates high risk.…”
Section: Optical Signaling Readout-based Nanobiosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Meanwhile, Yang and colleagues proposed controlled DNA valency and enhanced hydrogelation to modify the detection range and yield the limit of detection (LOD) ranging from fM to nM. 29,37 We also developed an enthalpy and entropy synergistic regulated strategy to control the response performance of the DNA motif. 38 The study revealed that by controlling the loop length and mismatched bases in the stem, the acid dissociation constant could be tuned arbitrarily to increase or decrease sensitivity while simultaneously improving the dynamic range.…”
Section: ■ Introductionmentioning
confidence: 99%